Law on import tax and export tax - The National Assembly (2005)
This Law provides for import tax and export tax applicable to goods imported or exported through Vietnam's border-gates or borders; goods sold, purchased or exchanged by border residents and other sold, purchased or exchanged goods, which are considered import or export goods